Tinjauan Pengelolaan Limbah Kain Perca Pada Home Industri Menurut Hukum Lingkungan - Ophie Virginia; Nur Qoilun (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
This study examines the management of textile waste from a home-based garment business, UD Mode Jahit, located in Taman District, Sepanjang Village, from the perspective of environmental law based on Law Number 32 of 2009, Law Number 18 of 2008, and Government Regulation Number 22 of 2021. The problem addressed in this research is the suboptimal management of textile waste, which has the potential to cause environmental impacts in residential areas. This study employs an empirical legal research method with a descriptive qualitative approach through observation, interviews, and documentation. The results show that waste in the form of fabric scraps, threads, and mixed textile materials is partially reused or sold to collectors, while the remaining waste is temporarily stored, disposed of together with household waste, or burned in small quantities. This condition indicates that waste management has not been carried out in a planned and sustainable manner in accordance with applicable legal regulations. Therefore, increased awareness among business operators and the implementation of a more structured and environmentally friendly waste management system are required.